Healing verses: ethnography of popular healing practices in visual poetry - DOI: 10.3395/reciis.v3i2.253en - Messias Basques (Instituto de Comunicação e Informação Científica e Tecnológica em Saúde (Icict) da Fundação Oswaldo Cruz (Fiocruz), 2009)
This study intends to analyze 'cordel'1 booklets on popular healing practices, and their visual-poetic production. This work assumes that popular healing practices found, in the universe of booklets, an important means to disseminate cases, stories, and history. Not only does it attempt to depict the divergence that imparted a secondary role to these practices; it questions, above all, the epistemological asymmetry that lies between scientific 'knowledge' and popular 'belief '. It is also important to question the traditional classification both of this wisdom and of this poetic genre in the superstition and folklore categories, since such judgment would imply loss of that which may be characterized as the expression of a witchery of practices, in addition to the lack of observance of the singularity and status of poetry, and the relationship of alterity resulting from speech in writing and its pictorial resources. With this purpose an ethnography will be made in the IEB-USP Archive - which hosts collections of rolled up booklets - with the intention of confronting the initial purpose of the survey in the face of the appropriation of this poetic genre in the project Third Trip of Poets to Brazil - Northeast - Caravan of Health (PERNAMBUCO, 1994), which resulted in the production of booklets on preventive medicine.